The prevalence of thrombocytopenia at a primary care HIV clinic in South Africa - possible implications for neuraxial anaesthesia - Steadman, Carl (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMed)-- Stellenbosch University, 2017.